2018
DOI: 10.1037/rep0000170
|View full text |Cite
|
Sign up to set email alerts
|

The German Multidimensional Attitude Scale Toward Persons With Disabilities (G-MAS): A factor analytical study among high-school students.

Abstract: Findings are discussed in light of the outcome that, of the studied sample, less than 1/3 of the students clearly expresses positive attitudes toward persons with disabilities. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 28 publications
(58 reference statements)
3
25
1
7
Order By: Relevance
“…The Polish version of the MAS was characterized by a similar factor structure as the original MAS from 2007 [13], including 3 subscales (affect, cognition, behaviour) and 34 items, and a satisfactory reliability. The obtained results suggest that the MAS-PL can be used to assess attitudes towards PWD in Poland, which can then be compared with international data collected in research with the use of the MAS scale [26,[28][29][30][31][32][33][34][35][36]. In the majority of population studies, the other language versions showed the same factor structure -i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Polish version of the MAS was characterized by a similar factor structure as the original MAS from 2007 [13], including 3 subscales (affect, cognition, behaviour) and 34 items, and a satisfactory reliability. The obtained results suggest that the MAS-PL can be used to assess attitudes towards PWD in Poland, which can then be compared with international data collected in research with the use of the MAS scale [26,[28][29][30][31][32][33][34][35][36]. In the majority of population studies, the other language versions showed the same factor structure -i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A 4-dimensional MAS (negative affect, calm, positive cognition, behavioural avoidance) with modified items was first introduced in the Spanish version in 2013 [31-30 items], then implemented in the French version in 2015 [26 -20 items], and the German version in 2018 [35-16 items]. In recent studies, researchers using Confirmatory Factor Analysis demonstrated a better fit of the 4-factor model (Comparative Fit Index CFI>.95) [35]. However, studies on the Polish3-factor model showed that each scale achieved a reliability coefficient exceeding α = 0.8, and the addition of subsequent sub-scales failed to yield satisfactory effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Multidimensional Attitudes Scale (MAS), developed by Findler, Vilchinsky, and Werner (2007), is one of the most prevalent, versatile, and comprehensive instruments used to measure negative attitudes. This scale has been translated into various languages: Spanish (Stevens et al, 2013), French (Dachez, Ndobo, & Ameline, 2015), Korean (Lu & Kim, 2017), and German (Wöhrle, Franke, & Kissgen, 2018). Although the original MAS (Findler et al, 2007) was developed for measuring attitudes toward persons with physical disabilities, it has also been applied to attitudes toward persons with ASD (Dachez & Ndobo, 2018;Dachez et al, 2015).…”
mentioning
confidence: 99%
“…Com relação aos objectivos apresentados na proposta -Tabela 7os juízes valoraram positivamente os diferentes itens afirmando por unanimidade (5±0,00) que se adequavam às necessidades do desenho da mesma (4.7). Igualmente, os expertos estiveram de acordo em que a metodologia incluía objectivos relacionados às três dimensões da atitude (4.4, 4.5 e 4.6) indicando valores acumulados acima de 100 e um CV inferior a 10% De facto, um dos aspectos fundamentais da metodologia baseia-se no desenvolvimento das atitudes desde uma perspectiva multidimensional, a qual esta assente nos vários estudos específicos (Kim et al, 2015;Radlińska, Starkowska, Kożybska, Flaga-Gieruszyńska, & Karakiewicz, 2020;Wöhrle, Franke, & Kissgen, 2018). Neste sentido, a concordância entre juízes concorre para confirmar a validade da proposta em análise (Crespo, 2007;Galicia Alarcón, Balderrama Trápaga, & Edel Navarro, 2017;Souza et al, 2017).…”
Section: Procedimentosunclassified